Sponsored Influencer Vlogs and Young Viewers: When Sponsorship Disclosure Does not Enhance Advertising Literacy, and Parental Mediation Backfires. Issue 1 (February 2022) - Harms, Bianca; Hoekstra, Janny C.; Bijmolt, Tammo H. A.
Using unique data from 609 parent–daughter (8–16 years of age) dyads, in an online experiment we studied two pivotal antecedents of young viewers' cognitive advertising literacy: influencer-generated sponsorship disclosure (written and/or spoken) and parental mediation style (active or restrictive). A between-subjects, single-factor design was applied with three experimental conditions: written disclosure, spoken disclosure, and both written and spoken disclosure, and a control condition—no disclosure. Variance-based partial least squares structural equation modeling in Smart-PLS 3.0 shows that policy makers' and parental measures to safeguard young consumers from negative consequences of sponsored vlogs can lead to unanticipated effects. While the combination of written and spoken sponsorship disclosure information as well as an active parental mediation style increase cognitive advertising literacy, restrictive parental mediation negatively affects cognitive advertising literacy. In addition, cognitive advertising literacy negatively affects young viewers' evaluation of the vlogger and positively affects the attitude toward the sponsored brand. Our findings provide important insights for parents, practitioners, and regulators and contribute to the discussion of how to make influencer marketing more effective and ethical.